The Translation of Culture-bound References for Dubbing: A Model for the Analysis - Satkauskaitė, Danguolė; Astrauskienė, Jurgita (Respectus Philologicus, 2022)
Culture-bound references receive considerable attention from translation scholars, as they are regarded as one of the most difficult challenges that translators face. However, most studies examine the transmission of culture-bound references to the target audience in literary texts, while research that would examine the translation of culture-bound references in audiovisual discourse involving additional constraints is somewhat limited. Dubbing is considered to be one of the most challenging modes of audiovisual translation, mainly due to the synchronization applied to it. This paper presents a model for the analysis of the translation of culture-bound references dedicated specifically to dubbing. The authors of the paper discuss the complexity of the concept of culture-bound references, their categorization and the taxonomies of their translation procedures. The article discusses the specifics of dubbing, the typology of synchronies applied in dubbing and restrictions posed by it on the translation of culture-bound references.
Keywords: audiovisual translation; dubbing; animation; culture-bound references